The effects of six-week pyramid resistance exercise program and supplementary nutrition on the increase in maximum strength of elite weight lifter - Reisi, J.; Marandi, S. M.; Dehghani, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The pyramid system is one of the advanced training systems in the field of body building and fitness that used for hypertrophy and muscle mass increase. The goal of this study was to examine the effect of the pyramid system and Consumption of ceratine mono-hydrate and carbohydrate Protein supplements on increasing the muscular strength and 1-repetition maximum. Methodology: for this purpose, 29 of the elite Pressers of Esfahan province (age:24.58 ±2.12, weight:87.86±6.46) were selected randomly and divided into 3 groups of resistance training+ supplementation(RTS N=10),resistance training ( RT=10) and control(N=9) groups.72 hours before the first exercise and 72 hours after the last exercise session they were taken a record for their chest press using 1-repetition maximum. Results: the findings of this study showed that there was a significant difference between the control and RTS group after going through a six-week resistance exercise program. However, there was no difference between the control and RT group (P > 0.05) and the level of progress in the RTS group was higher than in the other two groups (P < 0.05). Discussion: it seems that the combination of the pyramid system and ceratine supplements and carbohydrate protein mixtures causes an increase in muscular strength and 1RM in elite weight lifters and using pyramid system alone without the consumption of any food supplements has no effect on muscular strength in the elite weight lifters. Key words: Chest Press, Monohydrate Ceratine, Carbo-hydrate Protein, pyramid system